Implementation of the Saturday Cultural Program at Senior High Schools in Mataram City - Syifa Miftahul Amalia; Anik Widiastuti; Taat Wulandari (Journal of Innovation in Educational and Cultural Research, 2024)
In the era of globalization and rapid technological advancement, local culture is increasingly marginalized, leading to a diminished understanding among students. To address this issue, the West Nusa Tenggara Education and Culture Office introduced the Saturday Culture program to enhance students' cultural knowledge. This study aims to examine the program's implementation in senior high schools in Mataram City, using structural functionalism theory to explore the interactions within the school system that influence the program. Employing a quantitative descriptive method, the research involved 86 high school teachers selected through accidental sampling. Data collection was conducted via questionnaires distributed using Google Forms, and the analysis utilized descriptive statistical methods. The findings show that the program's overall implementation is rated as good, though certain areas require improvement. From the structural functionalism perspective, the program successfully fulfills four main functions: adaptation, goal achievement, integration, and latency maintenance. These outcomes demonstrate the program's ability to meet environmental demands, achieve educational goals related to culture, and foster student's character development. This research contributes to academic and cultural studies by highlighting the necessity for ongoing enhancement and stronger stakeholder collaboration to ensure the program's long-term effectiveness and sustainability.